Hepatic perihilar amphicrine cholangiocarcinoma: A case report - Thomas W. Czeczok; David J. Schembri-Wismayer; Thomas C. Smyrk; Mark J. Truty; Taofic Mounajjed (Elsevier, 2018)
Mixed neuroendocrine nonneuroendocrine neoplasms (MiNEN) are tumors composed of adenocarcinoma and neuroendocrine neoplasm and include collision, combined, and amphicrine. Within the hepatobiliary tree, tumors of this histologic type are extremely rare, particularly the amphicrine type. In this case study, we describe a 63-year-old man with a hepatic hilar amphicrine tumor. An initial diagnosis of neuroendocrine tumor was made based on biopsy (chromogranin and synaptophysin positivity). On resection, the tumor contained histologic features of both adenocarcinoma and neuroendocrine carcinoma. Immunohistochemically, all tumor cells expressed both chromogranin and synaptophysin, keratin 7, and Cam5.2. Mucin production was evident in both components demonstrated by mucicarmine stain. Albumin RNA in situ hybridization (ISH) was positive, supporting hepatic source. The tumor is classified as an amphicrine carcinoma given the dual expression of both adenocarcinoma and neuroendocrine markers in both components. This is the first amphicrine carcinoma of the hepatic hilum reported in the literature. Keywords: Cholangiocarcinoma, Mixed neuroendocrine-nonneuroendocrine carcinoma, Neuroendocrine tumor, Liver, Immunohistochemistry, Hepatobiliary